Analysis of the Effect of the Smart Indonesia Program, School Operational Assistance and Cashless Food Assistance on Reducing Poverty Reduction in North Sumatera - Handyton, Athoridho; Rahmadana, Muhammad Fitri; Harahap, Muhammad Yusuf; Rinaldi, Muammar (Advances in Social Sciences Research Journal, 2022)
The purpose of this study is to analyze Non-Cash Food Assistance, School Operational Assistance, and the Smart Indonesia Program that can affect poverty in North Sumatra during the 2019-2020 period. The type of data to be analyzed in this study is quantitative, namely secondary data obtained from various related agencies, namely BPS, Ministry of Education and Culture and other sources. The analysis in this study uses panel data regression. The results showed that the value of the coefficient of determination in the estimation results showed that the variables of poverty in North Sumatra could be explained by the variables of the Smart Indonesia program, school operational assistance, and non-cash food assistance that could be explained by the model used. The variables used to explain the poverty variable show the direction of the influence in accordance with the hypothesis, except for the Smart Indonesia Program variable which has a positive and significant influence. School Operational Assistance, has a negative and significant effect on poverty, Non-Cash Food Aid has a negative but not significant effect on poverty.